El motor metafórico en otoño, endechas de Javier Sologuren y el legado de Stéphane Mallarmé - Fernández Cozman, Camilo Rubén (2022)
Javier Sologuren is one of the most notable Latin American authors of the 20th century because he renewed Peruvian poetry during the 1950s, he was a well-known literary translator, and he rigorously reflected on the French symbolist and avant-garde poets. He published his collection of poems, Otoño, endechasin 1959 where the influence of Stéphane Mallarmé’s work is observed. The article is based on the proposals of the Cultural Rhetoric of Tomás Albaladejo regarding the use of the category of metaphorical motor. Based on the concept of cultural imaginary by Antonio García Berrio, it is pointed out how the metaphorical motor works in Sologuren’s poetry based on the notion of the instance of enunciation and reception. Sologuren draws on Mallarmé’s poetics andrestructures the French writer’s proposals tocreate a new metaphor. To substantiate his hypothesis, he also addresses the essays of the Peruvian poet where he talks about the peculiarities of Mallarmé and his ties with creators such as Paul Valéry or Guillaume Apollinaire.